Kajian Umur Simpan Bakso Ayam pada Suhu Pendinginan yang Berbeda - Sari Usih Natari; Bambang Kholiq Mutaqin (Jurnal Teknologi Hasil Peternakan, 2021)
The purpose of this research is to produce chicken meatball products with optimal low temperature and good characteristics. The research was conducted at the Nutrition and Sensory Assessment Laboratory, Department of Food Industry Technology, Padjadjaran University. The research method used is an experimental method with descriptive analysis. The research design used a completely rando-mized design (CRD) with 3 treatments and 6 replications. Treatment A = temperature -10OC, B = temperature 0OC, and C = temperature 10OC. The analysis used is the correlational test (causal relationship) and the hedonic test. The results showed a relationship between low temperature treatment and shelf life of chicken meatballs. Organoleptic obser-vations were the level of preference for taste, color, texture, and aroma. There is a relationship between low temperature treatment and shelf life of chicken meatballs. The shelf life of chicken meatballs at -10OC showed the highest value and was very significantly different from other treatments. This shows that the lower the storage temperature will be followed by the longer the shelf life of chicken meatballs.